2021
DOI: 10.1049/nbt2.12062
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and characterisation of solid lipid nanoparticles and investigation of toxicity against breast cancer cell line

Abstract: Solid lipid nanoparticles (SLNs) comprise non-toxic surface-active lipidic agents combined with appropriate ratios of drugs or essential oils. The goal of this research was to investigate the effects of the SLN synthesised using essential oils of Foeniculum vulgare on the MCF-7 breast cancer cell line. SLNs were prepared by homogenisation and ultrasound techniques and characterised by dynamic light scattering (DLS), zeta potential assessment, and transmission electron microscopy (TEM). 3-(4,5-dimethylthiazol-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…In this study, it was shown that treatment with nanoparticles in macrophage cells caused an imbalance in Bax/Bcl-2 expression as well as increased Caspase3 plus PARP expression ( Liang et al, 2019 ). In a study in 2021, the effect of SLN-NPs loaded with Foeniculum vulgare essential oil on MCF-7 cancer cells by stopping cells in the Sub-G1 phase was confirmed by flow cytometry ( Sharifalhoseini et al, 2021 ), which is similar to the present study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, it was shown that treatment with nanoparticles in macrophage cells caused an imbalance in Bax/Bcl-2 expression as well as increased Caspase3 plus PARP expression ( Liang et al, 2019 ). In a study in 2021, the effect of SLN-NPs loaded with Foeniculum vulgare essential oil on MCF-7 cancer cells by stopping cells in the Sub-G1 phase was confirmed by flow cytometry ( Sharifalhoseini et al, 2021 ), which is similar to the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Comparison of encapsulation efficiency of essential oil shows that in SEO-SCF-NPs, the loading rate is higher than FMO-SLNs, which is probably due to surface changes of SEO-SCF-NPs. In another study in 2021, SLN-NPs containing Foeniculum vulgar e essential oil with a size of 55.43 nm and a surface charge of −29.54 mV were synthesized ( Sharifalhoseini et al, 2021 ), which is smaller than SEO-SCF-NPs and has a negative surface charge. The differences can be attributed to the coating of SEO-SCF-NPs with CS-FA.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic and pro-apoptotic effects of SLN-containing drugs or surface-modified nanoparticles have been reported in various studies [ 46 48 ]. The pro-apoptotic effect of SLN-containing Foeniculum vulgare plant extract on MCF-7 cancer cells was investigated [ 49 ]. In 2019, Liang et al reported the pro-apoptotic effect of SLN nanoparticles by activating the internal pathways of apoptosis and disrupting the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Solid Lipid Nanoparticle (SLN) is a solid colloidal drug delivery system with a particle size of 10-1000 nm formed by solid natural or synthetic lipid-encapsulated drugs. It is the first generation of lipid nanoparticles [ 73 ]. It can effectively improve the solubility and bioavailability of NCTD.…”
Section: Passive Targeted Drug Delivery Systemsmentioning
confidence: 99%